MORPHOLOGICAL AND AGROCHEMICAL CHARACTERISTICS OF LITHOZEMS UNDER FOREST PLANTATIONS ON RECULTIVATED LANDS IN ZHYTOMYR POLISSIA - Strutinsky, O. V.; Tarnopilsky, P. B. (Forestry and Forest Melioration, 2018)
Introduction In the case of forest recultivation, fertile humic recultivating soil layer is not put in, and selective mining of minerals provides for the formation of the reclamation blade surface from a mixture of forest-suitable overburden rocks. Respectively, the lithozemic technogenic soils are dominating under forest plantations on recultivated lands. The information on their genesis is not sufficiently represented in the scientific literature, especially with regard to their formation under plantations of different composition and age and on different soil mixtures. Materials and Methods In order to comprehensively evaluate the results of forest reclamation on recultivated and undisturbed lands a number of sample plots were laid out in the stands of different age and composition the forestry fund of Shershnivske forestry in Korostenske Forestry and Hunting Enterprise. The sample plots were established in planted Scots pine (Pinus sylvestris L.), black alder (Alnus glutinosa (L.) Gaerth.), and silver birch (Betula pendula Roth) with alder stands and in natural birch stands. The age of the stands was 9–37. The pine plantation on undisturbed lands was 86-year-old. We determined forest mensuration indexes and described the morphological structure of the technogenic soil profiles. To study agrochemical properties of the soils the soil samples were taken from every genetic horizon and, in some soil sections, every 10–20 cm to a depth of 110–120 cm. Results The growing stock of 37-year-old planting birch-alder stands was only 44.6% of the stock of pine plantation of a similar age. The stock of 31-year-old pure pine plantation was more than 1.5 times higher than the stock of 34-year-old pure black alder plantation: 155 m3.ha-1 vs 101 m3.ha-1. Nine-year-old planted pine stand had the best growth. Percentage of average stock increment was 11.3 % and of current stock increment, 20.4 %. As the age of the plantation increases, the intensity of growth decreases. In 86-year-old pine plantation grown on undisturbed lands the percentage of average stock increment was 1.2 % and of current stock increment, 0.9 %. The planted pine stands grown more intensively as compared with alder and birch plantations. The morphological structure of heterogeneous lithozems formed under forest plantations and their agrochemical characteristics have been studied. It was established that the genetic horizons of technogenic soils are already evident under 20–30-year-old plantations. The highest content of humus and extractable nitrogen and potassium was found in the upper humus horizons in plantations of III–IV age classes. The content of humus in the upper horizons of soil profile under forest plantations was in the range from 0.84 to 4.12 % and, on all sample plots, significantly exceeded the content in the horizons that lied below the upper humus horizon in technogenic soil mixtures and zonal soils where its percentage ranged from 0.14 to 0.5 %. A high positive correlation was found between the contents of Nk and the extractable K2O, r = 0.77. Conclusions In the stands of a similar age, the productivity of pine plantations on the recultivated lands was higher in comparison with planted alder-birch and pure alder stands, and natural birch stands. The genetic horizons of technogenic soils can be determined under 20–30-years-old plantations. The highest contents of humus, extractable nitrogen and potassium were observed in the upper humus horizons in plantations of the III–IV age classes. In pure alder plantations, these are the highest. There are no clearly visible tendencies in P2O5 content change in the horizons. The content depends on the chemical properties of the geological layer, which is deposited on the surface and dominates in the composition of soil mixtures. 2 Figs., 2 Tables, 17 Refs.